Dr. Joseph Kasule and Dr. Joschka Philipps on public intellectualism - Kasule, Joseph; Philipps, Joschka (Cluster Conversations, 2024)
In this episode, Cluster fellow Dr. Josph Kasule talks with his host Junior Research Group Leader Dr. Joschka Philipps about Kasule’s research in general and the latest book project “Intimate colonialities, public intellectualism and political revolution in Uganda” that he has been working on during his fellowship in Bayreuth.